Managing diversified firms through socio-cultural mechanisms: A focus on Korean Chaebols - Ji-hwan Lee (Management Revue, 2007)
Based on theoretical considerations, this article investigates the socio-cultural mechanisms through which diversified firms are effectively managed without loss of control. Empirical results from extensive questionnaire surveys in Korea and the U.S. show that socio-cultural mechanisms such as shared values and corporate-level training were significantly and positively associated with divisional performance. In addition, sociocultural mechanisms appear to have unequal effects on the corporate performance in societies with different cultural contexts. Statistical results show that socio-cultural mechanisms worked better in chaebols than in large U.S. firms, possibly because such mechanisms positively interact with high-context culture.
Keywords: 650; diversified firm; Chaebol; socio-cultural mechanism; shared value; inter-divisional interaction; Diversity Management; Konglomerat; Interkulturelles Management; Shareholder Value; Südkorea